Participatory diagnosis to revitalize the performance of irrigation schemes in the Sahel: experiences from Burkina Faso and Niger - Sally, Hilmy; Levite, Herve (2011)
This article presents the preliminary results of a multi-partner action-research project, funded by USAID and jointly implemented by the International Water Management Institute (IWMI) and the Permanent Interstate Committee for Drought Control in the Sahel (CILSS). The project is implemented in two pilot countries, Niger and Burkina Faso in partnership with the respective irrigation agencies, the national ICID committees and the national agriculture research systems. The underlying hypothesis of the project is that the active participation of farmers in multidisciplinary performance analysis and diagnosis of their irrigation schemes will trigger a renewed awareness and enthusiasm to revitalize these schemes. The Participatory Rapid Diagnosis and Action Plan (PRDA) methodology is used for this purpose. This approach is well-regarded in West Africa and many experts have been already trained through the regional association on irrigation and drainage (RAID/ARID). Professionals from ICID committees carried out the diagnoses together with representatives of farmers. Five medium size (70 to 500 ha) public irrigation schemes were assessed in Niger and Burkina Faso with this method. One striking result is that farmers' involvement in the participatory diagnosis has raised their own awareness about the strengths and weaknesses of their schemes; in most cases they expressed willingness to take effective remedial action. However, it became evident that there is poor knowledge about the actual functioning of the schemes due to lack of monitoring by the managing agency and the farmers. Operation and maintenance of the irrigation facilities as well as administration and financial management of their organizations also pose major challenges for the farmers. The diagnostic exercise has also encouraged government to reengage in these schemes with a view to improving their performance by undertaking actions such as repairs and rehabilitation of infrastructure and farmer training.